Measurement of ocular torsion variation following superior oblique tenectomy - Ducca,Bruna Lana (2014)
Purposes: To objectively evaluate the torsional effect of the superior oblique muscle-weakening surgery using the tenectomy technique proposed by Souza-Dias. Methods: The present prospective study included 10 patients (20 eyes) with horizontal strabismus, bilateral superior oblique overaction and A-pattern of 15 to 30 prism diopters who underwent superior oblique tenectomy. Objective assessment of ocular torsion was performed by retinography immediately before and one month after surgery. The amount of ocular torsion was determined by measuring the angle formed by a horizontal line drawn across the geometric center of the optic disc and a second line connecting this point to the fovea. Results: The median preoperative angle was 5.56° in the right eyes and -3.43° in the left eyes. The median postoperative angle was 1.84° in the right eyes and -3.12° in the left eyes. The angle variation was statistically significant in both eyes (p=0.012 and p=0.01, respectively). Conclusion: The present study suggests that superior oblique tenectomy has an extorter effect, decreasing the intorsion detected on overaction of this muscle.